مصطلح ذوي القربى والأرحام والطريقة الشرعية في التواصل معهم عند فقهاء المذاهب: دراسة فقهية: The Concept of Relatives and the Legal Framework for Interacting with them as Interpreted by Scholars from various schools of Thought: A Jurisprudential Study - Hafsat Sulaiman Idris,; Nik Yusri Musa, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث صلة الأقارب وذوي الأرحام من أهم المقاصد التي تدعو الشريعة الإسلامية إلى تقويتها وترسيخها في المجتمع المسلم، وهي من أعظم الشعائر الاجتماعية التي أحال الإسلام أتباعه الاهتمام بها من أجل الإبقاء على الأُسرة والمجتمعات من الانهيار والدمار لذا هدفت الدراسة إلى بيان ذوي القربى والأرحام التي توصل وطرق صلتهم عند فقهاء المذاهب، وتمكن مشكلة الدراسة في الفكاك التي تحدث حول ذوي القربى والأرحام وعدم المعرفة بعضهم البعض وعدم الفهم للحقوق ذوي القربى ومعرفة الطريقة الشرعية في التواصل معهم ، وتبرز أهمية الدراسة في تسليط الضوء على طرق صلة ذوي القربى والأرحام. ولقد اتبعت الدراسة المنهج التحليلي، وتوصلت الدراسة إلى العديد من النتائج من بينها أن الأرحام هم الأقارب الذين نشأت القرابة بينهم بالنسب لا السبب كالرضاع والزواج وأن لفظ الأقارب فيشمل كل من جمع معك صلة نسبية أم سببية، ويشتمل القرابة المكانية كالجوار وأن أحرى درجة صلة الأرحام الوالدين ثم الأرحام المحرمة ثم غير المحرمة ثم بقية الأقارب وأن طرق صلة الأرحام تنقسم إلى قسمين: الصلة المالية والصلة غير المالية وأن فترة التواصل راجعة لعرف المجتمع. ولقد أوصت الدراسة بالعمل على توثيق العلاقات بين ذوي القربى والأرحام، من خلال اللقاءات الدورية، والاجتماعات الهادفة، وكذلك إنشاء صندوق للتكافل العائلي لمساعدة الأقارب المحتاجين. ABSTRACT The bond with family members is a fundamental objective emphasized by Islamic law to fortify and develop the Muslim community. It serves as a significant social practice within Islam, focusing on the preservation of familial ties and the prevention of societal disintegration. Hence, the primary goal of this investigation is to elucidate the connections among relatives and the methods of maintaining these relationships. Scholars from various Islamic sects identify the key issue as the conflicts arising within family connections due to lack of familiarity, ignorance of each other's rights, and unawareness of the appropriate legal approaches for interaction. This research underscores the significance of illuminating the strategies for engaging with and fostering relationships with relatives. The investigation adopted an analytical approach and yielded numerous findings. These findings indicated that relatives are individuals linked by lineage rather than by factors like breastfeeding or marriage. Additionally, the term "relatives" encompasses individuals with a familial or causal connection, including those with spatial kinship like neighbors. Furthermore, there tends to be a stronger bond between parents and relatives. The study then classified relatives into forbidden, non-forbidden, and other categories. It also delineated two forms of connecting relatives: financial and non-financial relationships, with the frequency of interactions being influenced by societal customs. Recommendations from the study included enhancing relationships among relatives through regular and purposeful gatherings, along with establishing a family solidarity fund to aid relatives in need.